Physical and Magnetic Properties of Barium Calcium Hexaferrite Nano-particles Synthesized by Water-in-oil Reverse Micelle and Co-precipitation Techniques - Jotania, R. B.; Khomane, R. B.; Deshpande, A. S.; Chauhan, C. C.; Kulkarni, B. D. (Journal of Scientific Research, 2008)
BaCaB2BFeB16BOB27B hexaferrite particles were prepared using two different techniques namely (i) reverse micelle and (ii) co-precipitation with and without presence of surfactants (cationic, anionic and nonionic). The precipitate was calcinated at 950ËC for 4 hours and characterized by using various instrumental techniques. The structural studies of the samples were studied by using XRD and SEM. The field dependent magnetic properties of prepared Ba-Ca hexaferrite powder was investigated at room temperature by using vibrating sample magnetometer. It has been observed that the type of surfactant plays a crucial role in deciding the morphology of the particles. There is significant change in crystallite size of the resultant Ba-Ca hexaferrite prepared in presence of anionic surfactant sodium dodecyl sulfate (SDS) and reverse micelle route. The samples prepared in presence of cationic and non ionic surfactants show agglomerated large particles. Magnetic study reveals that the value of anisotropy constant (K) depends on the type of surfactant used. The sample prepared in presence of nonionic surfactant Polyethylene glycol sorbitan monooleate (Tween 80) shows low anisotropy constant (0.26×10P-3P HAP2P/kg) where as the sample prepared in presence of SDS surfactant exhibits high anisotropy constant (3.26×10P-3 PHAP2P/kg) compared to normal sample (0.41 ×10P-3P HAP2P/kg). Keywords: Barium calcium hexaferrite particles; Surfactants; Structural and magnetic properties. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i1.1684